Meningkatkan Kemampuan Koginitif Anak melalui Permainan Tebak Angka - Pujiningsih Pujiningsih; Subawi Subawi (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2017)
This research is to enhance cognitive abilities, especially the early childhood’s ability to recognize numbers in playgroup Bina Bhakti Sari Purwosari Tlogowungu by using the number guessing game with plasticine or playdough props. Based on the cycle I and cycle II showing their improved cognitive ability in recognizing the concept of numbers in children KB Bina Bhakti Sari Purwosari Tlogowungu year 2016 / 2017. The average percentage increase in cognitive abilities in recognizing the concept of numbers of pre-cycle by 15%, in the first cycle of 50%, and the second cycle of 85%. Thus the guessing game figures using playdough props can improve cognitive abilities in recognizing the concept of numbers in playgroup Bina Bhakti Sari Purwosari Tlogowungu Year 2016/2017, through the steps as follows: 1) Researchers prepare settings and props are used; 2) Researchers demonstrate game activities to be undertaken; 3) The researcher invites children to play guess the numbers to form the numbers using plasticine; 4) Researchers and child make conclusions about the results of the activities carried out; 5) Researchers are giving rewards to children who are able to do the activities well, and motivate children who have not been able to carry out activities.